The Oxford handbook of publishing / edited by Angus Phillips and Michael Bhaskar - Kristina Silaj (Vjesnik Bibliotekara Hrvatske)
The Oxford handbook of publishing / edited by Angus Phillips and Michael Bhaskar. Oxford University Press, 2019. 480 str. ISBN 9780198794202